THE USE OF ADJUSTED READING MATERIALS IN THE TEACHING OF READINGCOMPREHENSION (RETAIN, 2013)
Adjusted Reading Materials for Reading Comprehension1THE USE OF ADJUSTED READING MATERIALS IN THE TEACHING OF READINGCOMPREHENSIONRestu Santyarini092084013English Education, Faculty of Language and Art, State University of Surabayarestubelle.santya@gmail.comDosen Pembimbing:Prof. Dr. Susanto, M. Pd.English Department, Faculty of Language and Art, State University of SurabayaAbstrakPenggunaan materi yang terlalu sulit oleh guru ketika mengajar reading menjadi alasan kenapa siswatidak dapat memahami teks dengan baik. Mereka menemukan banyak kesulitan ketika membaca teksnaratif yang diberikan. Guru harus merivisi RPP sebelumnya dengan memilih materi yang disesuaikanyang sejalan dengan kemampuan, kebutuhan dan ketertarikan siswa. Riset ini merupakan penelitiantindakan kelas yang hanya terdiri dari satu siklus. Ini disebabkan karena hasil pembelajaran menunjukkanbahwa tujuan pembelajaran telah dicapai. Riset ini diadakan di kelas VIII di salah satu SMP di Ngawi.Peneliti melakukan kolaborasi dengan guru dalam melaksanakan proses belajar mengajar. Penelitimenggunakan catatan lapangan tidak terstruktur untuk mengumpulkan data. Data harus dipilah dandiklasifikasikan menjadi data yang relevan dan tidak relevan. Kemudian data yang relevan akandiklasifikasikan dan dianalisis berdasarkan rumusan masalah. Hasil pengamatan menunjukkan bahwapenggunaan materi membaca yang sesuai membantu siswa untuk mengkategorisasikan teks naratifberdasarkan strukturnya, mengidentifikasi pesan moral dari teks naratif, menjawab pertanyaan seputarteks naratif dan menyimpulkan teks naratif.Kata Kunci: Penggunaan, Materi Membaca yang Sesuai, Pemahaman MembacaAbstractThe use of difficult narrative materials by the teacher in the teaching reading seems to be the reason whythe students cannot comprehend the text well. They found many difficulties in reading the narrative textgiven. The teacher should revise the previous lesson plan by choosing the adjusted reading materials whichin accordance with the students’ ability, need and interest. This research is a classroom action research withone cycle only. It was because the result of the study indicated that the goals of the study have beenaccomplished. This research was conducted at class VIII in one of junior high school in Ngawi. Theresearcher made collaboration with the teacher in conducting the teaching and learning process. Theresearcher used unstructured field notes to collect the data. The data had to be sorted and classified tochoose the relevant data and un-relevant data. Then the relevant data will be classified and analyzed basedon the research questions. The result of the observation indicated that the use of adjusted reading materialin the revised lesson plan helped the students in categorizing the narrative text based on its genericstructure, identifying the moral value of the narrative text, answering the question of the narrative text aswell as inferring the narrative text.Keywords: The use, Adjusted Reading Material, Reading Comprehension.INTRODUCTIONBackground of StudyStudents’ comprehension is the ultimate goal for thestudents when they do learn reading skill. It is the processof the readers to construct the meaning of the text theyread. Iwai (2010) states reading comprehension is basedon using the appropriate meaning-making processes fromthe printed messages. From Iwai’s statement it could beindicated that reading comprehension involves thepassage, the reader, and the context. The readersconstruct meanings of the passage using their backgroundknowledge, analyzing words, inferring the text, andidentifying key vocabulary or information. From thoseexplanations it could be concluded that readingcomprehension needs readers’ thinking and reasoning inorder to does it well. Since they must activate what theyhave known to build the meaning of the passage withoutknowing the meaning of each word. They relate theirknowledge and the context of the passage to build themeaning of whole.Ejournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216In one of small towns in East Java, there is a juniorhigh school which locates in the edge of big road ofSurabaya-Solo. Because of its location, this school isvery crowded. The teaching of English lesson in thisschool is conducted two times a week. One of the classesin this school is the eighth grade of C which consists of25 students, 14 females and 11 males. The class is largeenough for teaching and learning process. This class isnot completed with an AC, a LCD projector, as well as aspeaker. The students have arranged the chairs and tableswell in order to make them study easily. They mix theirseats so that the clever students will spread with the lowand medium students. When the teacher taught the basiccompetence 11.3 which about responding the meaningand rhetorical action of a short simple essay accurately,fluently and in the context of everyday life in the form ofrecount and narrative, she gave a narrative text to them,then she asked them to comprehend the text. The teacherused clear and loud voice during teaching learningprocess; however it was not enough to make the studentsunderstand the text well. Besides the fact indicates that inthe process of the teacher guiding them to comprehendthe text, there were several students who felt difficult tounderstand the text. Although there were some studentswho actively guessed the meaning of the text, there weremore students who were silent or talking to their friends.It made them cannot complete the task well. The teacherused three-phase technique, speech, questions-answersand task gift to teach reading. It seemed to be boringactivities for the students because they had lessopportunity to take part in the learning process.At that time, the teacher explained about narrativetext. However the narrative texts given to the studentswere very difficult for them. It was very confusing thestudents. The text used by the teacher was out of theircapability. They had to depend on the dictionary to knowthe meaning of words. It seemed to be boring for them.As the result, they stopped finding the meaning in thedictionary and started talking to others. It was one of thereasons why the students found difficulties duringreading class. They spent most of their time to find themeaning of the words than understand what the text talkabout. In other cases, there were some parts of the lessonplan that needed to be revised. It included the indicatorsand learning objectives. The indicators in the lesson planwere not specific enough. She only stated the studentscould identify the information, the aim and the languagefeatures of the functional text. How the students wouldidentify this kind of text without knowing what the textis. Besides, the objectives of study she designed were notbased on the indicators. It seemed that they were fromdifferent part. It was important for her to design theobjectives of the study from the indicators. So she couldmeasure whether the indicators have been reached by thestudents or not by looking to the objectives of the study.Furthermore, learning activities of the lesson plan wereonly teacher activities. There had to be students’activities too since in the teaching learning process themain actors are the students. The teacher is only theassistant who will help them when they find difficulties.Whereas the assessment in the lesson plan was onlyproduct assessment, there was no process assessment. Inthe teaching and learning activities, the most importantthing was in the process. It was not only the students’result that could be used as the measurement of thesuccessful learning. It also could be seen from theprocess. It was the reason why process assessment wasvery needed to be stated in the lesson plan.The revised lesson plan was given to the teacher asthe solution to the problem faced by her. Choosing theadjusted reading material for the students was theimportant thing to do. It should be easier material thatcould help them to understand what narrative actually is.It should be familiar to them so that they couldcomprehend it well. It also included formulating morespecific indicators based on the basic competence,adjusting the learning objectives to the indicators,designing the learning activities which will encouragestudents to participate as well as doing the processassessment correctly. The new learning activities weredivided into 2 tasks. The first task was applying pairwork. The students were asked to work in pair, then theygot a narrative from the teacher and their job was tocomprehend the text given. The second was applyingQuiz. To do quiz, the teacher divided the class into twobig groups. Every group got a text. Then the member ofeach group made a question to be asked to the oppositeteam. The team that could get biggest was the winner.During the quiz was running, the teacher was being themoderator of the two groups.The students can be called as successful readerswhen they can comprehend all the component of the text.They know what the text about. They are capable toanswer the questions related to the text (the explicitmeaning) as well as differentiate connotation and implicitmeaning of the text. From the rational above, it wasnecessary to conduct a research of the used of theappropriate material in teaching reading comprehension.How do the students respond toward the use ofappropriate material in the teaching of readingcomprehension? This study focused on how the studentscategorize the narrative text based on its genericstructure, how the students identify the moral value of thenarrative text, how the students answer when they getquestions from the teacher and how the students makeinferences while reading the narrative text.Review LiteratureThe ultimate goal of learning a language is to beable to comprehend and produce it in unrehearsedsituation, which demands both receptive and productivecreativity (Brown: 2000). Based on that statement, weknow that someone can be said learning a language ifhe/she can use it in every situation. However in thereading process, they do not only extract the meaning ofevery word but also connect the information they havegot from the text with their own prior knowledge. Pang,Muaka, Bernhardt, & Kamil (2003) state reading is acomplex activity that involves both perception andthought. From their statement we know that the readers’knowledge also play a role to help them understand thetext more. They have had prior knowledge in the form ofAdjusted Reading Materials for Reading Comprehension3perception. It is about what they have known. It may berelated to the new information stated in the text. Thenthey will start to think in order to get the meaning fromwritten text they read. It may make them understand thetext easier. Based on those explanations, the writerconcludes that reading is an active activity of seeking theinformation stated on the text and relating to their ownprior knowledge.Reading comprehension is the ability to understanda written passage of text. It allows readers to interact withthe text in a meaningful way. It is the bridge from passivereading to active reading. Active readers will not readfrom letters and words but from characters and contexts.For many, it also unlocks the door to a lifetime of readingrecreation and enjoyment. Supporting to that, Pardo(2004) says that comprehension is a process in whichreaders construct meaning by interacting with the textthrough the combination of prior knowledge and previousexperience, information in the text, and the stance thereader takes in relationship to the text. Before reading atext, readers have their own knowledge. In the process ofcomprehending, this knowledge will be very useful forthem. The combination of readers’ prior knowledge andtext’s information will be a great factor to build meaningof the text. The goal of teaching reading comprehensionstrategies is to give readers the tools which they need tobe effective readers and independent learners (Moreillon:2007). Reading itself is not an activity of getting fixedmeaning from written texts. The readers may use theirprior knowledge to support them in understanding thetext. In the process of reading, sometimes readers do notonly get a text with familiar words but also a text withunfamiliar words. They is not necessarily to read andunderstand the meaning of every word. They only need tofind the main idea of the text so that they can make asummarize about it.The material that should be taught in reading lessonmust be in accordance with the students’ interests andbackgrounds. In spite of it all, the teacher should alsoconsider the applicable curriculum. According to theprevailing curriculum, the material to be taught is anarrative text. So here the teacher should present thenarrative text that can attract students as well as notcontrary to the background of the students. This willmake the students more interested in reading activities.Iwai (2007) states the teacher needs to be aware in howthe students relate their prior knowledge and interact witha text critically, so that it guides them to have deeperunderstanding of texts and to become more powerfulreaders in other types of reading materials. Basically themore the students know about the material they are goingto read, the more successful readers they will be. It isbecause they do not need to struggle to comprehend thetexts. Only by reading the title, they will know what willhappen next. It is the way where their prior knowledgetakes role most.There are some studies which are conducted in theimplementation of fun reading comprehension teaching.The recent study was done by Akgün (1997) whichconcludes that the teacher must try to use fun activities inthe classes before she makes the necessary changesaccording to the specific needs and attitudes of your ownstudents. Other study was done by Raman (2004). Itconcludes that using reading quiz in the reading class isone way of motivating students to read and sustainingtheir interest in reading.The followings are the steps of teaching readingcomprehension adapted from Valette & Disick (1972)and Brown (2000). They can be done in the teachingreading comprehension using adjusted reading materials.The first step to do is pre-reading activities. Here, theteacher finds an interesting passage, which may appeal tomost of your students. By doing that, the teacher tries toactivate the students’ prior knowledge. Besides, theteacher needs to introduce the topic of the passage,encourage skimming, scanning, and predicting. Thestudents can bring the best of their knowledge and skillsto a passage when they can relieve to it. They will feelless unpleasant to the reading activities because they havealready been familiar with the passage which is usingtheir daily topics. The ultimate goal of reading iscomprehension, so in the second stage the teacher needsto direct the students to that goal. It can be adapted fromRaman (2004) who used quiz for his teaching of readingcomprehension. It can present fun while-readingactivities.METHODOLOGYResearch DesignThe design of this research is classroom actionresearch. According to Susanto (2007) classroom actionresearch is a research about the implementation ofteaching and learning process in the classroom. It isconducted to improve the quality of education byevaluating the previous unsuccessful study. It must be aproblem why the study is unsuccessful. It means that theproblem of the research comes from the classroom itself.Wallace (1998) also explains that action research isdifferent with other researchs in that it nearly alwaysarises from some spesific problem or issue arissing out ofusual practice. Therefore it focuses in the problem in itsapproach and practices in its intended outcomes. Thoseexplanantions give clear descriptions why in doing thisresearch the researcher needs to collaborate with theteacher of the class. They become partners for this study.It is because the teacher is someone who knows thestudents’ ability and behavior in the class.Setting of the StudyThe setting of the study was class VIII of SMPNegeri 2 Geneng. The researcher chose this class becausebased on the teacher’s information this class had problemsin the teaching and learning process. This class consists of25 students, 14 females and 11 males. It is large enoughfor teaching and learning process. It is not completed withan AC, a LCD projector, as well as a speaker. Thestudents have arranged the chairs and tables well in orderEjournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216to make them study easily. They mix their seats so that theclever students will spread with the low and mediumstudents. It is purposed to make the class go smoothly. Itseems not to work because several students feel difficultto comprehend the narrative text given by the teacher.Although there are some students who actively guess themeaning of the text, there are more students who are silentor talking to their friends. It make them cannot completethe task well and the class be crowded.Research ProceduresThis classroom action research has some steps.According to Susanto (2007), those steps are planning,implementation, observation and reflection in the field andreflection stage.1. Planning StageIn this stage, the researcher looked for someonewho could be a partner of this research. This partnerhad to be a teacher. She is needed as the requirementof Classroom Action Research that is collaborativeand classroom-based. The teacher explained herproblem during the learning process. This problemwas identified and evaluated by the researcher andthe teacher. Then they formulated the researchproblem in order to be solved by using classroomaction research. They prepared all the things whichwere used during the learning process. It consisted ofreformulating the new lesson plan. It concerned withthe learning materials which were used by theteacher.After making the revised lesson plan, theresearcher and the teacher set the criteria of thestudy. These criteria were in line with researchquestions of the study. They were used to measurethe students’ comprehension. The following are thecriteria of the study1. The first criterion was based on the firstresearch question, “1.2.1. To what extent arethe students able to categorize the narrativetext based on its generic structure?”. It meansthat the ultimate goal of the students learningwas the students were able to categorize thenarrative text based on its generic structures.The text used for the first criterion was SnowWhite. Students were required to categorizethe text of Snow White given by the teacher.The students were considered to be able tomeet the target of the first research question if75% of the number of students (22 students)was able to categorize narrative text based onits generic structure correctly; that isorientation, complication and resolution.2. The second criterion was according to thesecond research question, “1.2.2. To whatextent are the students able to identify themoral value of the narrative text?”. The goalof the study was the students could identify themoral value of the narrative text. Here, theresearcher used two different texts, Mantu’sLittle Elephant and The Goose That LaidGolden Eggs. The reason why the researcherused two texts was because in the process oflearning, the teacher asked the students tomake two big groups. Each group got a text.The students were considered to be able tomeet the target of the second research questionif 75% of the number of students (22 students)was able to identify the moral value of thenarrative text correctly.3. The third criterion was based on the thirdresearch question, “1.2.3. To what extent arethe students able to answer the questions aboutthe narrative text given by the teacher?”. Theresult to be achieved was the students wereable to answer the questions about the giventext. Here, the researcher used the same text asthe text used in the second criterion becausethe second and third criteria would be achievedby students in the same task, which wasplaying quiz. But in this third criterion,students were stated being successful not onlyfrom their ability to answer questions, but alsoon their ability to ask questions. Students wereconsidered to meet the target of the thirdresearch question if 75% of the number ofmembers of each group (11 students in eachgroup) was able to ask questions and alsoanswer questions about the two texts properly.4. The fourth criterion was according to thefourth research question, “1.2.4. To whatextent are the students able to make inferenceswhile reading the narrative text given by theteacher?”. For the fourth criterion, theresearcher used the same text as the firstcriterion that was Snow White. This wasbecause the first and the fourth criteria weredone in the same task. Teacher asked studentsto work in pairs. Then they had to infer whatthey read as a single group. The students wereconsidered to be able to fulfill the fourthresearch question if 75% of the number of thestudents (22 students) was able to infer thenarrative text given by the teacher.In the revised lesson plan, the researcherdesigned the meeting into two. In the first meeting,the teacher gave two narrative texts to the studentsthat were Malin Kundang and Snow White. MalinKundang was used to explain the concept ofnarrative text to the students. After explaining, theteacher asked the students to work in pair to discussthe text of Snow White. While in the secondmeeting, the teacher gave two other texts to thestudents, Mantu’s Little Elephant and The GooseThat Laid Golden Eggs. They were asked to make aclass work then they had to make questions aboutAdjusted Reading Materials for Reading Comprehension5the text and asked them to their opposite group. Inconclusion the researcher set the revised lesson planwith two tasks of four different narrative texts intwo meetings. The researcher and the teacher alsoprepared field notes to write all information andeverything happened during teaching learningprocess. So it could be concluded that this stage wasthe stage where they made a new scenario of theteaching process.2. Implementation StageIt was the stage where the new scenario of theteaching process was implemented. Here, theteacher taught as she did regularly. She taught basedon the revised lesson plan which was formulated inthe planning stage. This stage was held in twomeeting. The first meeting was used by the teacherto explain about the concept of narrative.Example 1. Descriptive NoteCatatan Deskriptif:Guru kemudian menunjukkan slide yangsudah disiapkan, Didalam slide dijelaskanapa itu teks naratif, generic structure,tujuan komunikatif dan strukturkebahasaan dari teks naratif sekaligussebuah contoh teks naratif. Contoh yangdiberikan adalah cerita Malin Kundang.Selama menampilkan slide, guru jugamemberikan pertanyaan kepada siswanyamengenai apa yang ada di dalam slide.Guru : “Okay students, pay attention tothese slides please. Here, you can see thatnarrative text is the text for …Siswa : “Entertaining the readers”(serentak)Guru : “Good students. So if you want tobe entertained, you can read narrative text.What about its generic structure? Let’s goto the next slide. It consists of the first,orientation. It is about the openingparagraph where the characters of the storyare introduced. The second is complication.It is the part where the problems in thestory developed. The third or the last isresolution. What is resolution? Anyoneknows what is it?…….Here, the teacher ensured that all the studentshave good understanding of narrative text beforethey went to the next activity. The second meetingwas used to employ quiz.Example 2. Descriptive NoteCatatan Deskriptif:Guru menjelaskan apa yang akan dilakukanhari ini. Mereka akan mengadakan kuis.kemudian guru menjelaskan caramemainkannya. Siswa mendengarkandengan seksama penjelasan yang diberikanoleh guru. Salah satu siswa mengajukanpertanyaan ketika tidak mengertipenjelasan yang diberikan.Guru : “Okay class, we are going to have aquiz for today. I have divided youinto two groups. Then I will giveyou two texts. The first text willbelong to group one and the secondwill belong to group two. Then yourjob is to read the text and makequestions based on it. The questionsmust include comprehensionquestions, vocabulary items andgrammar items. The questions canbe in the form of true/false, yes/no,matching to synonyms, antonymsand so on. You may use dictionarywhile making questions. Eachmember of the group has tocontribute at least two questions.After having prepared the questions,you have to read the other half ofthe passage as you will have toanswer questions based on it. Anyquestions so far?”………..It was to reduce students’ boredom duringreading process. It also showed how the studentsunderstanding of narrative text delivered in the firstmeeting.3. Observation and Reflection in the Field StageThis stage was coincided with the implementationstage. It was done by the researcher. The researcherobserved the teaching learning process done by theteacher. She used field notes to take note about whathappened in the class during the teaching learningprocess.Example 4. Descriptive NoteCatatan Deskriptif:Guru melakukan apersepsi, ia menanyakanpada siswanya hal-hal seputar teks naratif.Guru : “Okay class, who knows what thenarrative text is?”Siswa : “The text for entertaining thereaders ma’am” (menjawab serentak)Guru : “That’s right. It is the text forentertaining its readers. What aboutthe generic structure?”Siswa : “Orientation, complication,resolution ma’am”. (beberapa siswa)Hanya beberapa siswa yang mampunenjawab pertanyaan dari guru mengenaigeneric structure dari teks naratif.Besides writing all the things happened, theresearcher also reflected the data which they havegotten from the implementation stage. The result ofthe reflection was realized in the form of reflectivedata.Example 4. Reflective NoteCatatan Reflektif:Guru melakukan apersepsi untukEjournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216mengetahui sejauh mana siswnya telahmemahami teks naratif. Hal inidimaksudkan agar tidak terjadipengulangan materi yang akan membuatsiswa bosan.4. ReflectionIt was the stage where the researcher and theteacher made a review of the data. They gaveexplanation of the data collected in the field notes.Then they analyzed the students’ feedback duringthe teaching learning process using appropriatematerial. This feedback was as the measurement ofhow the students’ comprehension.To measure the students’ comprehension, theresearcher and the teacher had to make the criteria.They were set from the research questions of thestudy. If the students could accomplish all thecriteria stated in the research questions, the cycle ofthe study was successful. From the first task, theresearcher indicated that 75% of the numbers of thestudents have been able to categorize the text ofSnow White based on its generic structure and makeinferences while reading the text. The second taskindicated that 75% of the numbers of the studentshave been able to identify the moral value of thetexts, Mantu’s Little Elephants and The Goose ThatLaid Golden Eggs, ask questions of the texts as wellas answer the questions. Those result indicated thatthe goals of the study have been accomplished. Sothe next cycle was not needed.Data Collection TechniqueThe researcher was the key instrument of the studywhile data collection technique for this study was byusing observation which was done in form of qualitativedata. Wallace (1998) states qualitative is used to describedata which are amenable to be counted or measured in anobjective war and are therefore “subjective”. Data will bepresented in the form of words, phrases or sentences.Meanwhile,The aimed of qualitative approaches is to offerdescriptions, interpretations and clarification ofnaturalistic social context. Qualitative research drawson the data collected by the researcher to make senseof the human behavior within the research context(Burns: 1999).The researcher used unstructured field notes to writeall the information and also everything happened duringthe teaching and learning process. Still according toWallace (1998) making field notes can prevent theresearcher from trouble and confusion in presenting datacaused by continuing to the next things. It helped her toorganize the data before the data was being analized. Thefield notes organized into descriptive and reflective notes.Descriptive note contains of the description of whathappens during the teaching and learning process (seeExample 3), while reflective note was used to write whatthe researcher’s opinions and comments about all theactivity in the teaching and learning process (seeExample 4).Data AnalysisAs Susanto (2007) states in his book that data whichthe researcher gets from the observation usingunstructured format is very plentiful, but not all the dataare relevant with the requirement, they need to beclassified and proceed systematically. The relevant datawould be classified based on the research question of thestudy. After reducing un-relevant data, the researcherclassified relevant data based on the research questions ofthe study. There were four research questions. The firstwas about students’ ability in categorizing a narrative textbased on its generic structure.The second data was about the students’ ability inidentifying the moral value of the narrative text. The thirdwas about the students’ ability in answering the questionsof the narrative text. The last was about the students’ability in inferring the narrative text.RESULTS AND DISCUSSIONThe Teaching Process of a Reading ClassBefore conducting classroom observations, theresearcher discussed with the teacher about the problemsencountered during the previous learning process. Afterthat the teacher gave the lesson plan used in the previousstudy. The researcher then examined all the data obtainedfrom the description of the teacher and the previouslesson plan. After that she could conclude that the reasonwhy students have difficulty in reading comprehensionwas due to materials using by the teacher too difficult.The text used was beyond the ability of her students. Thisresulted in many more students who were silent duringthe learning process. Moreover, some students spoke withtheir friends. They surrendered to read as bored and notinterested in the text provided by the teacher. Even ifthere were students who were reading, they weredependent on a dictionary to find the meaning of difficultwords. This was very time-consuming. As a result, thepurpose of reading that was comprehension was notachieved properly.Based on the previous lesson, the researcher madethe revised lesson plan. In her revised lesson plan theresearcher chose the appropriate material based on theteacher’s description of her students ability. This wasdone to make the students did not feel difficult tocomprehend the texts given. The researcher alsoreformulated more specific indicators based on the basiccompetence, adjusted the learning objectives to theindicators, and designed the learning activities whichwould encourage students to participate as well as do theprocess assessment correctly. Students’ activities focusedon making the students to comprehend the text. In thisstudy, the researcher made collaborative research withthe teacher. The teacher was the one who taught in thereading class. The researcher observed the teachinglearning process followed by the students and took fieldnotes based on it.Adjusted Reading Materials for Reading Comprehension7According to the observation done by the researcherand data in the field notes, the researcher could say thatthe students were very interested in doing readingactivities. They also had discussion with their couplefriend as well as their classmate in a big group. Thelearning process generally was running concussively.Although there were some students who founddifficulties, it did not disrupt the learning process inreading class. By doing group discussion, they couldlearn to work together with their friends. The smartstudents would help their friends who found difficulties.The role of teacher was also evident in the learningprocess. Although the students could learn independently,but the teacher kept her eyes on them when they haddiscussions. The questions that were not answered bygroup discussion then it will be answered by the teacher.The use of appropriate materials that were in the revisedlesson plan greatly helped students in reading class.The Students’ Ability in Categorizing the NarrativeText Based on Its Generic StructureThe reading activities which was followed by thestudents were based on the revised lesson plan (Appendix2) made by the researcher. When preparing revised lessonplan, the researcher should consider the appropriateindicators to make students understood the text properly.This indicator would be used to replace the indicatorsused by the teacher in the previous lesson plan. Based onthe basic competence the students would learn thenarrative text, the important thing to do was to introducethe narrative text itself to the students. It made them ableto know the generic structure of narrative text andcategorize text given by its generic structure. The data ofstudents' ability to categorize the narrative text based onits generic structure when they had discussion would bethe answer for the first research question.In the beginning of the class, the students were busywith themselves. It was because they used the languagelaboratory for today’s lesson. They needed few time to gothere and prepare themselves to get the lesson. Afterawhile they could pay attention to the teacher. Then thestudents were greeted by the teacher. (1)(1) TeacherStudentsTeacherChoirulTeacherStudentsTeacherStudentsAntokTeacher::::::::::“Assalamu’alaikum Wr. Wb.”.“Wa’alaikummusalam Wr.Wb.” (In choir)“Ayo Choirul silahkandipimpin untuk berdoa”“Before we start our lessontoday, let’s pray together. Praybegin. (Praying together)Finish.”“Good morning students, howare you today?”“Good morning ma’am, I’mfine, thank you.”“Do you fasting?”“Yeees Ma’am”“Ma’am fasting?”“Of course Antok, I do.This greeting purposed to warn the students that thelesson would be started. The teacher also asked thestudents to pray first before starting the lesson. Theteachers wanted to familiarize her students with goodhabits so that this habit would be instilled in students.After greeting, the teacher the students’ attendance listwas checked by the teacher. Then they got theexplanation about what they were going to do for thelesson that day. The teacher read the basic competenceand the learning objective for them. It was purposed toensure that all the students knew what they needed toachieve at the end of the study. However some studentscomplained to the teacher because they got many thingsto study. (2)(2) TMegaDiniT::::“Okay class, this is our basiccompetence for the lesson today.Merespon makna dan langkahretorika dalam esai pendeksederhana secara akurat, lancardan berterima yang berkaitandengan lingkungan sekitardalam teks berbentuk recountdan narrative. For today, we willlearn about narrative text. Afterstudying, you are expected to beable to recognize what narrativetext is, identify thecommunicative purpose ofnarrative text, identify thegeneric structure of narrativetext, identify the languagefeatures of narrative text and findall the information stated in thenarrative text.”“Waduh ma’am, kok banyakbanget yang harus dipelajari.”“Iya ma’am.”“Don’t worry students, we’ll doit slowly. You can ask questionif you don’t understand. Andremember, it is not as difficult asyou think.”Brown (2000) stated that teachers should subdividetheir techniques into pre-reading, during-reading, andafter-reading phases. It could be seen in dialogue (2) thatthe teacher had divided her technique into pre-readingphase. In this phase, she tried to tell the students aboutwhat they were going to do. Then she introduced thetopic for the lesson to the students that was aboutnarrative text. There were so many indicators that had tobe mastered by the students for the day. Some studentscomplained. But teachers could calm them well. Theteacher convinced the students that all these materialswould not be a big problem because they would learnslowly. This made the students feel comfortable with thelearning atmosphere in the classroom.After giving explanation about the basiccompetence and the learning objectives, the teacher gaveapperception for the students related to the goal theywanted to achieve. (3)Ejournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216(3) TSTS::::“Okay class, who knows what thenarrative text is?”“The text for entertaining thereaders ma’am” (In choir)“That’s right. It is the text forentertaining its readers. What aboutthe generic structure?”“Orientation, complication,resolution ma’am”. (Some students)Dialogue (3) indicated that not all the studentsanswered her question. It meant that not all the studentsknew about the generic structure of narrative text. Theyneeded more explanation from the teacher about narrativetext. Then the teacher showed the slides of narrative text.The slides explained about what the narrative text is, thegeneric structure of narrative text, the communicativepurpose of narrative text, language features of narrativetext as well as an example of narrative text. The examplegiven was the story Malin Kundang. During the slide wasshowed, the teacher also gave questions to the studentsabout what on the slide. (4)(4) TSTMegaTDiniTSTST:::::::::::“Okay students, pay attentionto these slides please. Here,you can see that narrative textis the text for … ““Entertaining the readers” (Inchoir)“Good students. So if you wantto be entertained, you can readnarrative text. What about itsgeneric structure? Let’s go tothe next slide. It consists of thefirst, orientation. It is about theopening paragraph where thecharacters of the story areintroduced. The second iscomplication. It is the partwhere the problems in the storydeveloped. The third or the lastis resolution. What isresolution? Anyone knowswhat is it?”“Problemnya diselesaikanma’am.”“Good Mega, Here inresolution, the problem of thestory is solved.”“Kalo sad ending gimanama’am?”“Good question Dini.Resolution of narrative text canbe better or worse. If it isbetter, it will be happy ending.If it is worse, … ““It will be sad ending ma’am.”(In choir)“Great students. Any questionsso far?”“No Ma’am”“The next is about theGaluhMegaTSTHoniYayankTAntokT::::::::::communicative purpose ofnarrative text. It is used toamuse, entertain and to dealwith an actual or vicariousexperience in different ways.Now I have question for youstudents, how are the languagefeatures of narrative text?”“Pake ed ed Ma’am”“Was were Ma’am”“Is it right? Let’s check in thisnext slide. The languagefeatures of narrative text areusing past tense. So Mega andGaluh are right. Yang pake edsama was atau were. It isbecause the story happened inthe past time. Another languagefeature is using pronoun. Whatis pronoun?”(Silent)“Kata ganti orang, such as I,we, she, he and it. Who canmention the example ofnarrative text?”“Cinderella Ma’am”“Malin Kundang”“Good, students. Okay, haveyou ever read the story ofMalin Kundang?”“Pernah ma’am, yang anakdurhaka itu kan ma’am?”“Yes, you’re right Antok.Malin Kundang is one of theexamples of narrative text. Youcan see in the slide.”To make them more understand about narrative text,the teacher used the story which is common for them.According to Brown (2000), the teacher had to balanceauthenticity and readability in choosing texts. The teachershould adjust the text given to the abilities and needs ofher students. By doing this, the students would be moreinterested to read a given text. The story used by theteacher is Malin Kundang. The students were interestedto this story because they could use their knowledge tocomprehend the text. Then each student accepted a copyof narrative text from the teacher. The teacher explainedthe generic structure of the narrative text based on thetext given. It made the students can understand each partof generic structure of narrative text easily. The teachertried to make her students reach the learning indicators.(5)(5) TDellaTUntari::::“It is the text of Malin Kundang.I’ll give you the copies. Pleasespread it out, Della.”(Spreading to her friends)“Okay class, now look at thetext you have got. Which one isthe orientation?”“Paragraf one Ma’am”Adjusted Reading Materials for Reading Comprehension9TUntariTJatraTJatraTSTClaraTS::::::::::::“Good Untari. How can you saylike that?”“Ehm anu Ma’am. Tokohnyamuncul di situ. Perkenalan”“Great Untari. So in the firstparagraph, the writer introducesthe characters of the story, thesetting and we can say it isintroduction. What about theconflict? Who knows?”(Raising hand)“Yes Jatra”“Paragraf dua sampe yangsebelumnya paragraph terakhirMa’am”“Good answer Jatra. And theresolution? Who knows?”(Raising hand)“Wow, many students raise theirhands. Good. Okay Clara, whatis the answer?”“Last paragraph Ma’am”“You are right Clara. I think allof you have understood aboutnarrative text well. Giveapplause for us”(Clapping hands)The students were asked to make pair group. Theygot another narrative text. This time the text was SnowWhite. They were asked to categorize narrative text theygot based on its generic structure. (6)(6) TSTChoirulTST:::::::“Okay students, please make acouple group. You may chooseit by yourself. Do it now!”(Making a couple group)“Help me to spread it out,Choirul. A text for eachgroup.”(Spreading the texts)“It is Snow White story. Yourjob is to categorize it based onthe generic structure. You canwork with your group. Anyquestions?”“No Ma’am”“Good, you can work it now”Dialogue (5) and (6) indicated that the teacher hastaught her students using “SQ3R” sequence. Accordingto Brown (2000) teacher should follow the “SQ3R”sequence in their teaching. It could be seen from theactivities she used for teaching reading. Firstly theteacher explained about the generic structure of narrativetext. She also gave several texts that were used to sharpenthe students’ understanding of narrative text. The step ofquestion was also used by the teacher. It was becausefrom the question that the students asked and answered,the teacher could measure how far the students haveunderstood the lesson.To make the students did not feel bored, the teacherasked students to create a group. In addition to that, thiswas done to make students able to work well together.Some students seemed to easily categorize the narrativetext based on its generic structure, but some students stillseemed difficult to do so. For this reason was why theteacher made the students work in groups. It wasintended that the students could help each other. Thestudents who already understood about narrative textcould help their friends who still did not understand aboutit. (7)(7) GaluhClaraGaluhClaraGaluhClara:::::::Paragraf yang “She fled to thedungeon beneath the castle.There the Queen mixed a potionthat would change her into anold hag. Then she took an appleand slowly dipped it into anotherpotion sampai habis itu masukcomplication ya?”“Iya, itu complicationnya.”“Bawahnya itu masa jugacomplication lagi Ra?”“Iyalah, kan dalam satu teksnarrative bisa punya lebih darisatu complication.”“Ada 4 complication ya berarti?““Nah itu bener. Bisa lohsebenarnya kamu.”The dialogue (7) showed that a student tried to helpanother. They discussed what they did not know. Brown(2000) explained teachers should use techniques that areintrinsically motivating. Divided the students to work ingroups was one of the ways in which the teacher couldmotivate her students. The students who were not able tocomprehend the text well would be motivated by a friendwho was able to comprehend the text well. This wouldimpact on the learning outcomes of students which thestudents were able to understand the reading text properly.In the discussion, there were several groups that bothmembers found difficulties in categorizing the genericstructure of the text. It was because they have not reallyunderstood what has been explained by the teacher. Thestudents who had difficulties ask the teacher for moreexplanation (8)(8) YossiaTYossiaT:::::“Ma’am, kalo dari orientationke complication itu adajedanya atau enggak”“What do you mean by Jeda?”“Itu loh Ma’am, kayaperalihan”“Orientation is the paragraphwhere the writer introduces thecharacter, the setting etc.While complication is theparagraph where the conflictEjournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216YossiaT::appears. So when you find aconflict in the paragraph youread, it means that it iscomplication. Is it clear?”“Oalaah gitu Ma’am. OkeMa’am, understand”“Good”After all students were finished with theirdiscussion, the teacher asked the students to discuss ittogether. What they have discussed with their groups.This was done in order that the students really understoodabout narrative text. Students seemed eager to discusswith the teacher. They wanted to show that they havemastered the material taught. (9)(9) TSTDodiTST:::::::“Okay students, have youfinished?”“Yes Ma’am”Great students. Now, we aregoing to discuss it. Okay Dodi,which one is the orientation?”Itu Ma’am, yang paragrafpertama. Yang long ago sampewas very cruel”“ Is it right students?“Yes, Ma’am“Okay class, go on to the next……” (Continuing to the nextdiscussion)At the end of the discussion session, the studentsseemed to understand about the generic structure ofnarrative text. It could be seen from the many studentswho had been able to categorize narrative texts providedby the teacher based on its generic structure. It wassupported by dialogue (7), dialogue (8) and dialogue (9).The teacher did not have trouble when asking herstudents to discuss the generic structure of narrative text.When they still did not find the answer of theirdiscussion, then the student might ask the teacher. It waswhich made the students able to properly categorize thenarrative text. Then the teacher could continue to the nextactivities.The Students’ Ability in Identifying the Moral Valueof the Narrative TextThe second research question to be answered by theresearcher was the ability of students in identifying themoral value of the narrative text. Based on the descriptionof teachers when teaching reading using previous lessonplan, many students did not comprehend the narrative textdelivered by the teacher, especially to identify the moralvalue of the narrative text itself. Then the researcherchanged the narrative text given to students in the revisedlesson plan. This was done to make students were able tocomprehend the text better as well as able to identify themoral value of narrative text. Brown (2000) stated in hisbook that it needs the follow-up of the activities of readingthey did. The teacher had to make a follow up activitiesafter the students did reading activities. It will help her toknow her students’ reading understanding of the text.What they have got of the text.Then the teacher re-explained the last material toassure that all students have understood the concept ofnarrative text well. Later, she went on to the nextactivities. Akgün (1997) did a study which concluded thatthe teacher must try to use fun activities in the classesbefore she makes the necessary changes according to thespecific needs and attitudes of your own students. The funactivity which was used by the teacher was Quiz. The useof “Quiz” was adapted from Raman (2004). He said thatthe used of Quiz Game could motivate students to readand sustain their interest in reading. When reading becamea game it took away the monotony that they appeared toassociate with the act of engaging with the printedpage. Then the teacher divided the students into twogroups. It was a big group. The students then gatheredwith their group. It took a rather long time because somestudents did not get along with the group. There weresome who did not join the group, but it could be overcomeafter the teacher warned them. (10)(10) TChoirulTJatraTJatraApriantiTJatraTSTHoniTYuli:::::::::::::::“Okay students, I will divideyou into two group”(Demonstrating with hands)“Ma’am kelompoknya pilihsendiri atau dipilihkan?”“I’ve chosen the group for thisquiz. The first group consistsof the students who were ineven numbers. The secondgroup consists of the studentswho were in odd number… “(Raising hand) “Ma’am”“Yes Jatra”“Even number itu apaMa’am?”“Nomer genap ya Ma’am”“Yes, you’re right Aprianti.Even number means nomergenap, while odd numbermeans nomer ganjil. Get it?”“Oalah. Ngobrol dong Ma’amkalo gitu maksudnya”“Now, all of you please gatherwith your group”(Noisy)“Ssssst, hayo Honi where isyour group? Go go, get yourgroup.”“Yes yes Ma’am”“Yuli, what are you doing?Stop talking get your groupright now”“Yes Ma’am” (Walking to hergroup)Then the teacher explained how to do quiz to thestudents. (11)(11) T : “Okay class, we are going tohave a quiz for today. I haveAdjusted Reading Materials for Reading Comprehension11LauraTLauraT::::divided you into two groups.Then I will give you two texts.The first text will belong togroup one and the second willbelong to group two. Then yourjob is to read the text and makequestions based on it. Thequestions must includecomprehension questions,vocabulary items and grammaritems. The questions can be inthe form of true/false, yes/no,matching to synonyms,antonyms and so on. You mayuse dictionary while makingquestions. Each member of thegroup has to contribute at leasttwo questions. After havingprepared the questions, youhave to read the other half ofthe passage as you will have toanswer questions based on it.Any questions so far?”“Ma’am, what iscomprehension question? ““Comprehension question is aquestion which is related to thetext. It can be explicit meaningwhich is written clearly in thepassage such as characters inthe story, or implicit meaningwhich is not written clearly inthe passage such as main idea,moral value and so on.”“Oh, pelajaran yang bisadiambil dari cerita gitu yaMa’am?”“You’re right Laura. Your timefor reading and preparing thequestions are only 15 minuteswhile for the next second textyou have only 5 minutes. Soyour time is only 20 minutes forall” (Demonstrating with hands)Dialogue (10) and dialogue (11) indicated that theteacher played the role as a leader of the class. She wascontrolling her students before letting them worked withthe group. Valette & Disick (1972) explained that readinginvolved internal behaviors. One of them was perceptionwhere the teacher introduced the language. In thedialogue 10, the teacher read the instruction for playingquiz. It was the teacher’s way to introduce to her studentsabout the quiz. How they could play the quiz. In addition,the teacher also used a simple instruction that was easilyunderstood by students. According to Brown (2000)teaching reading skill should be in an interactivecurriculum, in which the teacher used quiz to teachreading. Besides, she always remembered to use simpleinstructions for her quiz. It was because she knew that herstudents were lack of vocabularies. If she used thecomplicated instruction, her students would notunderstand what she said. It meant nothing.The students then got a text of narrative. They readit carefully. Each team also seemed keen to makequestions based on the text they read. They were quicklyable to make the question of the text. This was becausethey have already known about the concept of narrativetext. (12.1) & (12.2)Group 1(12.1) AntokOktaAntokFitri::::“Heh, kamu bikin pertanyaanapa?” (Looking at Okta’squestion)“Ealah Tok, baca dong. Bikinapa kek”“Fit, tanya apa dong?”“Siapa tokohnya aja Tok,nggak papa”(Other members of group one werediscussing)Group 2(12.2) WahyuMega::“Udah Meg?”“Udah. Heh kalian udahbelum bikin pertanyaannya?Buruan, mau abis waktunya”(Other members of group two werediscussing)After finished making question, they got anothertext from their opposite team. They read it more carefullybecause they would have questions about the text and hadto answer it correctly. Then the teacher explained therules of the game. The students could easily understandthe teacher’s explanation because she used simpleinstructions. After knowing the rules, they looked moreenthusiastic to play the quiz.During the quiz was held, many questions arose.Some questions could be easily answered, but there weresome questions that needed more understanding. (13.1) &(13.2)Group 1(13.1) DinaDodiTDinaTGroup2::::::“Why did the elephantscreech?”“Because they heard the wordsnack”“Is it correct Dina the answerfrom Dodi?”“Correct Ma’am”“So, group 2 gets 1 point”“Yeeeeee” (In choir)Group 2(13.2) MegaOktaTMega::::“What is moral value of thestory of the Goose that LaidGolden Eggs?”“Mmm, We should not begreedy”“Is it correct Mega theanswer from Okta?”“Correct Ma’am”Ejournal Unesa. Volume 01 Nomor 01 Tahun 2013, 0 - 216TGroup1::“So, group 1 gets 1 point”“Yeeeeee” (In choir)The dialogue above (13) showed that some studentshave been able to reach an understanding of the explicitmessage conveyed by the author. Taking from the resultsof the quiz, the teacher discussed with the studentswhether they still had difficulties or not. It was based onBrown (2000) statement, since reading was unobservableskill; the researcher indicated the students’comprehension from how the students gave responses totheir teacher. At first only a student who asked to theteacher, then another asked either. The students whoasked showed that he had understood what was beingtaught by the teacher. Then the teacher gave explanationclearly about the questions. (14)(14) DodiTMegaTOktaTChoirulTUntariTMegaTT + S:::::::::::::“Moral value itu apa?”“Good question Dodi. Moralvalue is the point of what wecan take from the story. Soyou explain about what youget after you read that story. Isthere any other questions?”Loh Ma’am kalo gitu tujuanpenulisan itu apa Ma’am?Beda ya sama moral value?”“The purpose of writing issomething which is conveyedby the writer to the reader.Whereas moral value is whatthe readers gain after reading /